Assessing the Rate of Social Phobia among Infertile Women - Mohsen Hojat (Journal of Global Pharma Technology, 2017)
Introduction although social phobia is considered mainly as behavioral disorder in the field of clinical psychology, it entails by social factors and in consequences that can be followed in the fields of social sciences and social psychology. Infertile women implicate in social phobia disorder; therefore, this study is designed to put into effect the rate of social phobia among infertile women. Materials and Methods The present study is a descriptive-analytical. It is carried out on 210 infertile women in Jahrom and Yazd. Utilized tool is SPIN questionnaire that its validity and reliability are confirmed. Data collection is inquired by educated group, and it is analyzed by software SPSS: 16. Findings Results indicate that infertile women implicate a high rate of social phobia, and there is significant relationship between social phobia and education, religiosity, and social support (p<0.05). Conclusion Due to high rate of social phobia among infertile women, it is recommended to consider social phobia and its increasing and decreasing variables, along with mental advisory and physical examination in fertility treatment clinics.Keywords: Social phobia, Religiosity, Social support, Socio-economic status, Infertility, Women.